Biochemical detection of E-ADA on Neospora caninum tachyzoites and the effects of a specific enzymatic inhibitor Detección bioquímica de E-ADA en taquizoitos de Neospora caninum y los efectos de un inhibidor enzimático específico - Tonin A.A. (2015)
Objective: This study aimed to investigate the presence and activity of the ecto adenosine deaminase (E-ADA) enzyme in tachyzoites of Neospora caninum (Nc-1 strain), as well as to assess the activity of a well-known E-ADA inhibitor, the deoxycoformycin. Materials and methods: The parasites were grown in cell culture, being subsequently separated in a pellet of tachyzoites, on which the E-ADA activity was tested using the concentrations 0 (control), 0.2, 0.4 and 0.8 mg mL-1. Results: The E-ADA showed high activity, progressively increasing its activity according to the enhancement of the protein concentration. The test was carried out with different concentrations of deoxycoformycin, showing that it was able to inhibit the E-ADA present on the free form of the parasite. Conclusions: Based on these results we conclude that the E-ADA is present on tachyzoites of N. caninum, and deoxycoformycin is able to inhibit this enzyme. In this sense, knowing the negative impact of N. caninum on reproductive issue in cattle (mainly abortion), might it is an alternative in order to deal with this parasitic infection.